Case studies of integration between activity-based demand models and multimodal assignment. (May 2022) - Gemma, A.; Mannini, L.; Busillo, V.; Cipriani, E.; Crisalli, U.
Abstract: Aiming at supporting decision makers in transport policy choices in an increasingly complex sequence of activities of our real day-life, this paper investigates the integration between Activity Based Model (ABM) and transport assignment by focusing on the multimodal demand-supply interaction to be used in more advanced simulation models. The consistency between ABM and assignment models is studied proposing a methodology that can be applied to large real size networks. A new formalization of integration of ABM with multimodal assignment is proposed, oriented to an easy-to-use and computationally faster application. The interaction between different modes sharing the same network facilities is considered, as well as crowding (public transport) and congestion (road) phenomena. The application to different real case studies in Qatar and in Rome are presented to show the promising results of the proposed approach for a better transport simulation in urban areas.